Analisa Laporan Keuangan Sistem Informasi Akuntansi Pendapatan Jasa Pada Harry Art Salon Dengan Zahir Accounting 5.1 - Saefudin, Dede Firmansyah; Wahyuni, Tri; Alifah, Alifah (PROFITABILITAS, 2021)
In the current era of globalization, information technology is advancing rapidly, as for computers which are devices that are created to facilitate human work, while making progress both in making hardware and software. Harry Art Salon is in need of an accounting application that supports the recording of transactions and making financial statements. For this reason the author tries to make a Final Project regarding accounting applications in the Harry Art Salon, which until now has not been computerized. Harry's Art Salon is a business that is engaged in services and product sales. Recording of transactions that occur and making financial statements are still done manually, starting from recording the receipt of cash transactions including service income and product sales and cash disbursements to the preparation of financial statements, making it possible during the process of recording errors and resulting in inaccurate financial statements so there was a delay in finding the required documents.Zahir accounting application accounting version 5.1 is the best solution to solve the problems that exist in this company, as well as with a computerized system can achieve an effective and efficient activity in supporting activities in this company.